Complicity in the Holocaust : churches and universities in Nazi Germany - Ericksen, Robert P. (New York : Cambridge University Press, 2012)
Robert Ericksen argues that enthusiasm for Hitler within churches and universities effectively gave Germans permission to participate in the Nazi regime.
Why the Holocaust matters in a century of death -- Churches and the rise of Hitler -- Universities and the rise of Hitler -- Consent and collaboration : the churches through 1945 -- The intellectual arm : universities through 1945 -- Repressing and reprocessing the past : denazification and its legacy of dissimulation -- t
Includes bibliographical references (pages 237-251) and index.
Keywords: Church and state -- Germany -- History -- 1933-1945.; National socialism and religion; Universities and colleges -- Germany -- History -- 20th century; Higher education and state -- Germany -- History -- 20th century; National socialism and education; Anti-Nazi movement -- Germany; Holocaust, Jewish (1939-1945) -- Germany; Anti-Nazi movement -- Germany; Church and state -- Germany -- History -- 1933-1945.; Higher education and state -- Germany -- History -- 20th century; Holocaust, Jewish (1939-1945) -- Germany; Universities and colleges -- Germany -- History -- 20th century; Anti-Nazi movement; Church and state; Higher education and state; National socialism and education; National socialism and religion; Universities and colleges; Germany; 1900 - 1952; History